How could health information exchange better meet the needs of care practitioners? - Kierkegaard, P.; Kaushal, R.; Vest, J.R. (Applied Clinical Informatics, 2014)
Background: Health information exchange (HIE) has the potential to improve the quality of health-care by enabling providers with better access to patient information from multiple sources at the point of care. However, HIE efforts have historically been difficult to establish in the US and the failure rates of organizations created to foster HIE have been high.Objectives: We sought to better understand how RHIO-based HIE systems were used in practice and the challenges care practitioners face using them. The objective of our study were to so investigate how HIE can better meet the needs of care practitioners.Methods: We performed a multiple-case study using qualitative methods in three communities in New York State. We conducted interviews onsite and by telephone with HIE users and non-users and observed the workflows of healthcare professionals at multiple healthcare organizations participating in a local HIE effort in New York State.Results: The empirical data analysis suggests that challenges still remain in increasing provider usage, optimizing HIE implementations and connecting HIE systems across geographic regions. Important determinants of system usage and perceived value includes users experienced level of available information and the fit of use for physician workflows.Conclusions: Challenges still remain in increasing provider adoption, optimizing HIE implementations, and demonstrating value. The inability to find information reduced usage of HIE. Healthcare organizations, HIE facilitating organizations, and states can help support HIE adoption by ensuring patient information is accessible to providers through increasing patient consents, fostering broader participation, and by ensuring systems are usable.Citation: Kierkegaard P, Kaushal R, Vest JR. How could health information exchange better meet the needs of care practitioners? Appl Clin Inf 2014; 5: 861–877http://dx.doi.org/10.4338/ACI-2014-06-RA-0055
Keywords: Health information exchange; consent model; evaluation studies; community; information systems